2007
DOI: 10.1074/jbc.m700569200
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Subcellular Localization of a Novel Nuclear Acetylcholinesterase Protein

Abstract: Acetylcholine is found in the nervous system and also in other cell types (endothelium, lymphocytes, and epithelial and blood cells), which are globally termed the non-neuronal cholinergic system. In this study we investigated the expression and subcellular localization of acetylcholinesterase (AChE) in endothelial cells. Our results show the expression of the 70-kDa AChE in both cytoplasmic and nuclear compartments. We also describe, for the first time, a nuclear and cytoskeleton-bound AChE isoform with ϳ55 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…The molecular form of 70 kDa is also expressed at cytoplasm and nuclear compartments, where the latter also expressed an AChE isoform with approximately 55 kDa [11]. We verified that the nuclear expression is not endothelial cell-specific but is also evidenced in nonneuronal and neuronal cells [11].…”
Section: Non-neuronal Cholinergic System (Nncs)supporting
confidence: 53%
“…The molecular form of 70 kDa is also expressed at cytoplasm and nuclear compartments, where the latter also expressed an AChE isoform with approximately 55 kDa [11]. We verified that the nuclear expression is not endothelial cell-specific but is also evidenced in nonneuronal and neuronal cells [11].…”
Section: Non-neuronal Cholinergic System (Nncs)supporting
confidence: 53%
“…In parallel to the definitive findings established for R-AChE [61], [65], evidence is only now accumulating that the C-terminal domain of T-AChE may also undergo proteolytic cleavage in vivo [41], [66][69]. This helical domain independently exhibits autonomous bioactivity comparable to many of the non-catalytic effects attributed to the intact T-isoform of AChE [29][31], [33], [35], [39], [61], [66], [70].…”
Section: Discussionmentioning
confidence: 90%
“…Certainly a number of transcription factors contain such motifs [89], most notably those involved in apoptosis [90]. Interestingly, it has been shown that T-AChE is translocated to the nucleus upon initiation of apoptosis [59], whilst a nuclear form of AChE has been identified in endothelial cells [69]. Given that the presence of AChE in the nucleus, particularly in non-neuronal cells, precludes its classical role in neurotransmission, it is reasonable to speculate that this molecule contributes in some capacity to the regulation of transcriptional events.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other pathways like PI3K/Akt , protein kinase C (PKC) (Birikh et al, 2002), Nrf2 (Kosaka et al, 2009) may be involved in such signaling. Moreover, PC12 cells have been shown to synthesize nuclear and cytoplasmic isoforms of AChE (Santos et al, 2007). In fact this enzyme is expressed in several molecular forms, with different structural features but identical catalytic sites (Schweitzer, 1993).…”
Section: Discussionmentioning
confidence: 98%